2004
DOI: 10.1073/pnas.0407297101
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of the Jun-induced oncogenic phenotype by enhanced synthesis of sialosyllactosylceramide (GM3 ganglioside)

Abstract: ganglioside-enriched microdomain ͉ tetraspanin ͉ integrin ͉ anchorage-independent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 37 publications
2
48
1
Order By: Relevance
“…Although we do not know at present the mechanism of the GM3 synthase activation by NEU3 silencing that seems contradictory from a physiological point of view, GM3 synthase activation would be necessary for apoptosis induction. In this context, our results are consistent with those by other investigators that GM3 synthase is upregulated during cell apoptosis (Sohn et al, 2006;Valaperta et al, 2006) and downregulated in malignant transformation (Watanabe et al, 2002;Miura et al, 2004). GM3 synthase activation in our experiments, however, occurred in cancer cell death, and in neuronal cell death in the report of Sohn et al (2006).…”
Section: Discussionsupporting
confidence: 82%
“…Although we do not know at present the mechanism of the GM3 synthase activation by NEU3 silencing that seems contradictory from a physiological point of view, GM3 synthase activation would be necessary for apoptosis induction. In this context, our results are consistent with those by other investigators that GM3 synthase is upregulated during cell apoptosis (Sohn et al, 2006;Valaperta et al, 2006) and downregulated in malignant transformation (Watanabe et al, 2002;Miura et al, 2004). GM3 synthase activation in our experiments, however, occurred in cancer cell death, and in neuronal cell death in the report of Sohn et al (2006).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, various cell adhesion processes mediated by GSLs and TSP cause extensive phenotypic changes, including reversion from malignant to normal cell phenotype (8,9,25). In analogy, Bissell and colleagues (26,27) showed that functional antibodies directed to ␤1 integrin of breast cancer cells caused reversion, in vitro and in vivo, to normal cellular organization, indicating that malignancy may arise from disorganization of glycosynaptic microdomain rather than from changes in gene structure and expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that GSLs and glycosylation status of proteins play key roles in defining ontogenic development (12)(13)(14)(15), oncogenic transformation (26,27), and their phenotypic reversion (28,29). GSLs and protein glycosylation are therefore expected to play some role in EMT process.…”
Section: Discussionmentioning
confidence: 99%